The Philosophy Of The Value Of Harmony Of Pela Gandong Maluku Culture In The Perspective Of Contextual Theology - Tanamal, Nini Adelina (International Humanity Advance, Business & Sciences, 2025)
Religious and cultural tensions are not barriers but can facilitate religious people's expression of their faith. The theological context seeks to understand the Christian faith as a theological imperative. The Pela-Gandong tradition is an important element in Maluku culture that maintains kinship between Christian and Muslim communities. This tradition resolves conflicts, which contain the moral values of togetherness, unity, respect, equality, and peace. Misunderstanding leads to tension and conflict, especially between Christians and Muslims. After the conflict in Maluku in 1999-2002, the community realised the importance of revitalising the pela-gandong to maintain harmonious relations. The qualitative-inductive description methodology describes cultural and religious patterns in the contextual theology of fraternity in Maluku. Religious conflicts show that ignoring kinship in the Pela-Gandong tradition can cause religious divisions. Maintaining pangolins is the responsibility of all parties, including religious institutions in Maluku.